2021
DOI: 10.3390/ijms22073383
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting of Natural Compounds from Brazilian Cerrado Biome Plants in Human Cervical Cancer Cell Lines

Abstract: Cervical cancer is the third most common in Brazilian women. The chemotherapy used for the treatment of this disease can cause many side effects; then, to overcome this problem, new treatment options are necessary. Natural compounds represent one of the most promising sources for the development of new drugs. In this study, 13 different species of 6 families from the Brazilian Cerrado vegetation biome were screened against human cervical cancer cell lines (CCC). Some of these species were also evaluated in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The present study observed the poorest in vitro inhibitory activity for the B. a ungulata, A. fraxinifolium , S. guianensis, B. variegata candida, and X. aromatica crude leaf extracts toward the glioma cell lines. Therefore, although we have not observed cytotoxic effects for these crude extracts in gliomas, many may have action on other tumor types [ 57 , 58 , 59 , 60 , 61 , 62 ]. Recent studies published by our group revealed the importance of the diversity of secondary compounds in different crude extracts and their selective antitumor potential.…”
Section: Discussionmentioning
confidence: 75%
“…The present study observed the poorest in vitro inhibitory activity for the B. a ungulata, A. fraxinifolium , S. guianensis, B. variegata candida, and X. aromatica crude leaf extracts toward the glioma cell lines. Therefore, although we have not observed cytotoxic effects for these crude extracts in gliomas, many may have action on other tumor types [ 57 , 58 , 59 , 60 , 61 , 62 ]. Recent studies published by our group revealed the importance of the diversity of secondary compounds in different crude extracts and their selective antitumor potential.…”
Section: Discussionmentioning
confidence: 75%
“…The normality of the residuals (Shapiro-Wilk test, p>0.05) and the homogeneity of variances (Cochran test, p>0.05) of the data were tested. A one-way ANOVA followed by Dunnett's test (p<0.05) was used to determine significant differences between the organic and control extracts, and a factorial ANOVA followed by Tukey's test (p≤0.05) was bioactive molecules for the development of new anticancer drugs (Silva et al, 2020;Rosa et al, 2021), while Qualea cordata Spreng. (Vochysiaceae), known as "carvãozinho", has antioxidant properties (Carnevale Neto et al, 2013) as well as antimicrobial, antiulcer, anticonvulsant, and analgesic activity (Carli et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rosa et al [56], when evaluating the cytotoxicity of crude extracts of two species of Miconia (M. albicans and M. chamissois), found that the species showed IC 50 values lower than 30 µg/mL against the cell lines of human cervical cancer.…”
Section: Cytotoxicitymentioning
confidence: 99%